Implementation of Content Language Integrated Learning Approach in Reading Skills and Communication Skills of Elementary School Students (Universitas Negeri Semarang, 2020)
In an era of disruption, the skills needed by students include reading and communication. One approach that is believed to be able to practice reading and communication skills is the content language integrated learning approach. This study aims to analyze and identify the effectiveness of a content language integrated learning approach on reading and communication skills for third grade elementary school students. The research design was pre-experimental and the sampling technique used purposive sampling. This study involved 2 elementary schools with a sample size of 99 students. The data collection techniques used were tests, performance assessment, and documentation. The data obtained were analyzed using paired t-test and N-Gain test. The results showed that the implementation of the integrated content language learning approach was able to improve the students 'reading test results and students' communication performance assessments. The finding proves that the integrated language learning approach is effective for training the reading and communication skills of third grade elementary school students.